Association of Knowledge, Attitude and Practice of Cleaning Service with the Amount of Mosquito Larvae in Water Container At Bhayangkara Hospital, Palembang, Indonesia - Chairil Anwar; Putri Arini; Husnil Farouk; Novrikasari Novrikasari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Bacgkround: Efforts in the eradication of mosquito breeding have been done, but have not shown maximum results due to lack of community participation caused by several factors, such as lack of knowledge, attitude and practice that are considered to play important role in reducing the incidence of vector-borne diseases transmitted by mosquitoes. This study aimed was to determine the relationship of knowledge, attitude and practice of cleaning services with the amount of mosquito larvae at water container around Bhayangkara Hospital Palembang. Populations in this study were 25 cleaning services in Bhayangkara Hospital Palembang. Methods: Samples in this study were all populations taken by using total sampling technique. Data included the number and types of water containers, the number and species of mosquito larvae found in the water containers, and data of knowledge, attitude and practice of cleaning services. The results were analysed using Kruskal-Wallis statistic test. Results: There were 75 water containers, 63 water containers were indoors, one of them contains larvae, and 12 water containers were outdoors, the type of two outdoors water containers that contained larvae were plastic buckets. Total larvae that found were 16 larvae of Aedes aegypti. Based on Kruskal-Wallis statistic test, there was no average difference between the number of mosquito larvae based on knowledge with p>alpha± (0.072>0.05), and there was an average difference between the number of mosquito larvae based on attitudewith p<alpha± (0.006>0.05) and practice with p<alpha± (0.019<0.05). Conclusion: There was a negative association between attitude and practice against the number of mosquito larvae, but not with knowledge.